Pengaruh Penambahan Variasi Abu Tempurung Kelapa Terhadap Karakteristik Mortar - Mauludiyana, Gita; Trimurtiningrum, Retno; Sutriono, Bantot; Rochmah, Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Awareness of the importance of sustainable construction practices and research to explore alternative materials or waste that can be recovered to reduce material use and waste. This was done to evaluate coconut shell ash waste as a partial additive to cement in mortar mixtures. The research carried out aimed to determine the results of the influence of coconut shell ash waste on the absorption value to obtain overall analysis results on mortar mixtures using coconut shell ash additives with variations of 0%, 2.5%, 5%, 7.5%, 10%. The results obtained on the effect of adding coconut shell ash on the water absorption value show that a mixture of coconut shell ash can make mortar lose water more easily when compared to normal mortar, namely with the highest water absorption value of 9.307% in a mixture of 10% coconut shell ash.